Komitmen Pelayanan Perempuan di Gereja Anugerah Bentara Kristus Sola Gratia Pakasua: Kajian Teologi Feminis - Kamuhlut, Dian Apryostan Halena; Mosooli, Ermin Alperiana; Pohan, Juan Erwin (L-SAPIKA INDONESIA, 2025)
This study aims to analyze the factors influencing women’s ministry commitment at the Church of Anugerah Bentara Kristus (GABK) Sola Gratia Pakasua Congregation and to interpret this phenomenon through the lens of feminist theology. The research employed a mixed-methods approach using a sequential explanatory design. Quantitative data were collected through questionnaires administered to 38 active female church workers, while qualitative insights were obtained through in-depth interviews with five key informants. The results show that theological–doctrinal factors have the strongest influence on women’s ministry commitment (mean = 4.52), followed by socio–cultural, structural–organizational, personal–family, and psychological factors. Ministry is understood as a spiritual calling rooted in love and devotion to God rather than a mere institutional duty. From a feminist theological perspective, women’s active participation represents a theological and social transformation that embodies equality, solidarity, and spiritual resilience within a patriarchal structure. The findings affirm that women’s ministry reflects a liberating and contextual spirituality, providing significant implications for developing a participatory theology of ministry within local church contexts.